PROFIL BERPIKIR KREATIF SISWA KELAS VII B SMP NEGERI 6 JEMBER DALAM MEMECAHKAN MASALAH OPERASI PECAHAN BERDASARKAN TAHAPAN WALLAS DITINJAU DARI PERBEDAAN GENDER - Hendriyati, Nofiela Nuning; Trapsilasiwi, Dinawati; Susanto, Susanto (Department of Mathematics Education , University of Jember, 2017)
Abstract. The profile of creative thinking is a general person's view of human mental activity in solving mathematical problems with the ability to find various possible answers or find one answer in common but in various ways. This research aims to describe the profile of students' creative thinking based on Wallas Stage in solving mathematical problems of fractional operations based on gender differences. This research was conducted in Junior High School 6 Jember. Research subjects are all students of class VII B which consists of 27 female students and 11 male students. Interviewing process was conducted using Snowball Throwing method in which subject is randomly taken until finally 3 male students and 3 female students has been obtained as the subjects of the interview. Data collection is done through test and interviews. The results of this research showed that male and female students have been through four stages of creative thinking according to Wallas namely the preparation stage, incubation stage, illumination stage and verification phase. Male students are able to write down what is known and asked in the question well but explain the purpose of the question less fluently (preparation), through the process of short-while brooding (incubation), obtain one idea of ​​correct solution (illumination), less detailed and coherently write the steps of problem solving, and has reviewed the answer (verification). Female students can write down what is known and asked in the question completely and fluently explain the purpose of the question (preparation), through process of long-while brooding (incubation), obtain one idea of ​​correct solution and coherently write the steps of problem solving (illumination), And has reviewed the answer by recalculating the results of the work (verification). Keywords: Creative Thinking, The Process of Solving Mathematical Problems, Wallas Stage, Gender